2022
DOI: 10.3390/agriculture12111788
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rice Yield and Grain Quality to Combined Nitrogen Application Rate and Planting Density in Saline Area

Abstract: To determine the combining effects of nitrogen application rate and planting density on rice yield and grain quality formation under salinity conditions, a field experiment was conducted in the coastal saline area using Oryza sativa L. cv. Nangeng 9108 from 2019 to 2020. The experiment was designed with six nitrogen rates (0, 210, 255, 300, 345, and 390 kg ha−1; denoted as N0-N390, respectively) and two transplanting densities (334,000 and 278,000 hills ha−1; denoted as D1 and D2, respectively). The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The leaf area index, nitrogen uptake, agronomic efficiency, and recovery efficiency were also positively correlated with grain yield. In contrast, nitrogen uptake and leaf area index showed a significant negative correlation with internal N use efficiency (Chen et al, 2022). Ahmed et al (2016) found a significant interaction between the N rate and grain yield of crops.…”
Section: Correlation Analysismentioning
confidence: 84%
“…The leaf area index, nitrogen uptake, agronomic efficiency, and recovery efficiency were also positively correlated with grain yield. In contrast, nitrogen uptake and leaf area index showed a significant negative correlation with internal N use efficiency (Chen et al, 2022). Ahmed et al (2016) found a significant interaction between the N rate and grain yield of crops.…”
Section: Correlation Analysismentioning
confidence: 84%
“…Differences in planting density cause changes in the number of tillers during critical growth stages, affecting the morphological characteristics of stems, lignin, and cellulose composition, and lodging resistance, ultimately altering rice yield [9,29]. The combined application of silicon fertilizer is beneficial for normal physiological metabolism in rice and significantly promotes the growth of rice [9,30].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in planting density cause changes in the number of tillers during critical growth stages, affecting the morphological characteristics of stems, lignin, and cellulose composition, and lodging resistance, ultimately altering rice yield [9,29]. The combined application of silicon fertilizer is beneficial for normal physiological metabolism in rice and significantly promotes the growth of rice [9,30]. In this study, jointly increasing density, reducing N, and applying silicon fertilizer could promote changes in stem dynamics, plant morphology, and physiological characteristics during key growth stages, thereby affecting rice yield and lodging traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N application is an essential cultivation measure for regulating rice grain filling, endogenous hormone accumulation, and C and N metabolism. High N fertilization affects the grain filling balance, leading to slower grain filling and poor filling, resulting in a loose starch arrangement and increased chalkiness [ 18 ]; however, some studies have suggested that increasing N fertilization can prolong the effective filling period of inferior grains and reduce chalkiness formation [ 19 , 20 ]. The activities of cytokinins (ZRs), indole acetic acid (IAA), abscisic acid (ABA), gibberellin (GA), soluble starch synthase (SS), and starch-branching enzyme (BE) within the grain are strongly correlated with chalkiness during the pre-filling period, whereas the opposite is true during the post-filling period [ 21 ].…”
Section: Introductionmentioning
confidence: 99%